Ancestral role of Pax6 in chordate brain regionalization - Kozmik, Zbynek; Kozmikova, Iryna (Frontiers in Cell and Developmental Biology, 2024)
The Pax6 gene is essential for eye and brain development across various animal species. Here, we investigate the function of Pax6 in the development of the anterior central nervous system (CNS) of the invertebrate chordate amphioxus using CRISPR/Cas9-induced genome editing. Specifically, we examined Pax6 mutants featuring a 6 bp deletion encompassing two invariant amino acids in the conserved paired domain, hypothesized to impair Pax6 DNA-binding capacity and gene regulatory functions. Although this mutation did not result in gross morphological changes in amphioxus larvae, it demonstrated a reduced ability to activate Pax6-responsive reporter gene, suggesting a hypomorphic effect. Expression analysis in mutant larvae revealed changes in gene expression within the anterior CNS, supporting the conserved role of Pax6 gene in brain regionalization across chordates. Additionally, our findings lend support to the hypothesis of a zona limitans intrathalamica (ZLI)-like region in amphioxus, suggesting evolutionary continuity in brain patterning mechanisms. ZLI region, found in both hemichordates and vertebrates, functions as a key signaling center and serves as a restrictive boundary between major thalamic regions.